Berberine as a Potential Agent for the Treatment of Colorectal Cancer - Jiang, Xi; Jiang, Zhongxiu; Jiang, Min; Sun, Yan (Frontiers in Medicine, 2022)
Colorectal cancer (CRC) is one of the most commonly diagnosed and deadly malignancies in the world. The incidence of CRC has been increasing, especially in young people. Although great advance has been made to manage CRC, the prognosis is unfavorable. Numerous literatures have displayed that Berberine (BBR) is a safe and effective agent presenting significant anti-tumor effects. Nevertheless, the detailed underlying mechanism in treating CRC remains indistinct. In this review, we herein offer the beneficial evidence for utilization of BBR in the management and treatment of CRC, as well as provide the underlying mechanism(s). The review emphasizes several therapeutic effects of BBR and confirms that BBR could suppress CRC by modulating gene expression, cell cycle, inflammatory response, oxidative stress, and several signaling pathways. In addition, BBR also displays anti-tumor of CRC by regulating the gut microbiota and mucosal barrier function. This review emphasizes BBR could be used as a potentially effective and safe drug in CRC therapy.